Application of the Unus Testis Nullus Testis Principle in Corruption Crime Cases: Study of Decision No. 2677/PAN.PN.WII.UI/HK.2.2/VI/2025 - Budi Rahman (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Criminal procedure law in Indonesia mandates that judicial decisions be grounded on lawful evidence and the principle of minimum proof to uphold the rule of law. Specific Background In corruption crime adjudication, witness testimony constitutes valid evidence under the Criminal Procedure Code (KUHAP), yet it cannot stand alone due to the principle of unus testis nullus testis, which requires at least two lawful pieces of evidence to establish guilt. Knowledge Gap Limited doctrinal analysis has examined how this evidentiary principle is applied in concrete corruption cases involving multiple defendants and contested indictments by the Corruption Eradication Commission (KPK). Aims This study analyzes the application of the unus testis nullus testis principle in Decision No. 2677/PAN.PN.WII.UI/HK.2.2/VI/2025 and evaluates the evidentiary basis of the KPK Public Prosecutor’s indictment against Defendant IV FCR. Results Using normative juridical research with a statute approach, the study finds that only one witness alleged the transfer of IDR 30,000,000 to Defendant IV FCR, while other testimonies and documentary statements contradicted this claim. The indictment also demonstrated inconsistencies in legal reasoning and classification of evidence. Consequently, the evidentiary threshold under Articles 183 and 185 KUHAP was not fulfilled, rendering the charge unproven. Novelty This article provides a structured doctrinal examination of evidentiary insufficiency in a multi-defendant corruption trial through systematic interpretation of statutory provisions. Implications The findings reaffirm the centrality of corroborated evidence in corruption prosecutions and underscore the necessity of strict adherence to evidentiary standards to ensure legal certainty and judicial fairness. Highlights: A single uncorroborated testimony was insufficient to establish criminal liability. Contradictions among witness statements weakened the prosecutorial argument. The indictment failed to satisfy the statutory minimum proof requirement, leading to acquittal. Keywords: Indictment, Corruption, Public Prosecutor, Pleadings, Defendant